2011
DOI: 10.1016/j.ijthermalsci.2010.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Natural convection and wall condensation or evaporation in humid air-filled cavities subjected to wall temperature variations

Abstract: Heat and mass transfer by natural convection coupled to wall surface condensation or evaporation in a two-dimensional cavity subjected to uniform, but time-dependent wall temperatures is investigated numerically. At initial state, the cavity is filled with quiescent humid air at uniform temperature and density. By decreasing the wall temperature, condensation occurs at the four wall surfaces until an equilibrium thermodynamic state is reached. The walls are then Ra m solutal Rayleigh number,Sh local Sherwood … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 24 publications
0
26
0
Order By: Relevance
“…For dry air, c p (T ), k(T ) and µ(T ) are calculated according to the polynomial relationships given by Lide and Kehiaian [46], valid in the range [100 K, 600 K]. These properties variations were used in [47] where the specific relationships employed herein can be found.…”
Section: Dimensional Formmentioning
confidence: 99%
“…For dry air, c p (T ), k(T ) and µ(T ) are calculated according to the polynomial relationships given by Lide and Kehiaian [46], valid in the range [100 K, 600 K]. These properties variations were used in [47] where the specific relationships employed herein can be found.…”
Section: Dimensional Formmentioning
confidence: 99%
“…Some unsteady studies can be encountered concerning the specific case of enclosures filled with humid air, where some phase change can occur, as in [5][6][7][8], and in the references therein. Even if the majority of the reported studies refer to numerical works, some experimental work is also reported in the literature [1,9].…”
Section: Introductionmentioning
confidence: 99%
“…Present work is mainly motivated by the very recent one in [8], where the walls of a rectangular enclosure filled with humid air are subjected to some specific temperature variations, such that condensation or evaporation can occur at the walls. However, the circular cross section systems are also very interesting both in natural and engineered systems, and a similar study needs to be conducted concerning this geometry.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations